PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PENGEMBALIAN LABA ATAS ASET PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014 - 2019 - Indah Dwi Pratiwi; Rustam Effendi (JURNAL KOMPETITIF, 2021)
This study aims to determine: the effect of cash turnover and accounts receivable turnover, either simultaneously or partially, on the return on assets/profit returns on assets in pharmaceutical companies for the period 2014-2019. The sampling technique used was purposive sampling. The number of samples is 6 companies from 10 companies. This type of research is quantitative research and the type of data used is secondary data in the form of financial reports obtained through http://www.idx.co.id. The prerequisite analysis test used the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The data analysis technique used is multiple linear regression analysis.The statistical results show that simultaneously Cash Turnover and Accounts Receivable Turnover, either simultaneously or partially, Against Return On Assets / Returns of profit on Assets. This can be seen from the F test with a significant value of 0.039 <0.05. Then, the results of the coefficient of determination with an R Square value of 0.178 or equal to 17.8%. This value shows that Cash Turnover and Accounts Receivable Turnover affect the Return on Assets / Return on Assets by 17.8%, while the remaining 82.8% is influenced by other variables not examined. The statistical results of cash turnover partially have an effect on Return On Assets / Returns of profit on Assets. This can be seen from the t test with a significant value of 0.042 <0.05. The statistical results of accounts receivable turnover partially affect the Return on Assets / Returns of profit on Assets. This can be seen from the t test where the significant value is 0.039 <0.05.